STUDI KINERJA PELAYANAN ADMINISTRASI PADA MAHASISWA DI FAKULTAS FARMASI UNIVERSITAS MULAWARMAN - Muhammad Sunusi (Jurnal Administrative Reform, 2020)
The purpose of this study was to describe and analyze the performance of administrative services and to determine the inhibiting factors and supporting factors for the performance of administrative services at the Faculty of Pharmacy, Mulawarman University. This type of research is a qualitative descriptive. Types and sources of data used are primary data and were collected by purposive sampling and snowball sampling techniques. Data were analyzed using an interactive model. The results showed that the service performance for students at the Faculty of Pharmacy, Mulawarman University was following the procedures given to students. However, the services provided had not gone well because of the busy activities at the Faculty of Pharmacy. At the same time, the number of employees was small compared to the existing work units.Keyword : performance, administrative services